2007
DOI: 10.1016/j.bbabio.2007.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mitochondrial ATPase inhibitor protein (IF1) in the liver of late septic rats

Abstract: Sepsis and ensuing multiple organ failure continue to be the most leading cause of death in critically ill patients. Despite hepatocyte-related dysfunctions such as necrosis, apoptosis as well as mitochondrial damage are observed in the process of sepsis, the molecular mechanism of pathogenesis remains uncertain. We recently identified one of the differentially expressed genes, mitochondrial ATPase inhibitor protein (IF1) which is down-regulated in late septic liver. Hence, we further hypothesized that the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Rats and mice were most often studied. The effects of LPS and faecal peritonitis/CLP on mitochondria are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rats and mice were most often studied. The effects of LPS and faecal peritonitis/CLP on mitochondria are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Commin et al observed that rats that suffered CLP showed decreased activity of complex I, but not of the complexes II, III and IV in the electron transport chains [ 38 ]. In contrast, increased consumption of oxygen and breathing efficiency was demonstrated in the livers of septic rats [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in ATP content of roughly 15% has also been described during long-term anesthesia in healthy animals (48), possibly related to decreased perfusion of skeletal muscle (49). Nevertheless, decreased tissue ATP concentrations in septic rodents and pigs have been described, and arguments for substrate deficiency, exaggerated ATP hydrolysis, and decreased mitochondrial mass presented (50)(51)(52). In critically ill patients with sepsis and multiple organ failure, skeletal muscle mitochondrial enzyme activities were reduced and concentrations of ATP and creatine phosphate decreased (53).…”
Section: Discussionmentioning
confidence: 99%